On the basis of the hypothesis of local determinacy in the theory of elasto- plastic processes - Bich, Dao Huy; Thang, Duong Tat (Vietnam Journal of Mechanics, 1984)
The hypothesis of local determinancy gives concrete relations of elasto - Plastic processes, where functional of the qrientation and the capacity of stresses vector can be represented as a solution of the set of non - linear ordinary differential equations the behaviours of these functional are studied in the general case on this basis the boundary valuable problem in the theory of plasticity is exactly formulated.